Analysis of the Role of Financial Technology in Facilitating Access to Capital for MSMEs: A Case Study of Madiun City - Dinesh Basti Farani; Triana Prihatinta; Galuh Kusuma Wardani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the role of financial technology (fintech) in facilitating access to capital for Micro, Small, and Medium Enterprises (MSMEs) in Madiun City. The method used is a qualitative descriptive approach based on literature review and the latest secondary data from the Financial Services Authority (OJK), Bank Indonesia, and academic publications from the period 2023–2025. The results of the study indicate that fintech mechanisms, particularly peer-to-peer (P2P) lending, can improve MSME access to capital through fast fund disbursement processes, simple administrative requirements, and minimal physical collateral. In 2024, fintech lending to MSMEs in Madiun City reached Rp132 billion, a significant increase compared to the previous year. Nationally, outstanding P2P lending reached Rp80.07 trillion as of February 2025, with a significant contribution to the productive sector. However, low digital financial literacy, data security issues, and the prevalence of illegal lending remain major challenges. This study recommends structured improvements in digital financial literacy, strengthened adaptive oversight by the OJK, and multi-stakeholder collaboration between the government, fintech providers, and universities to build an inclusive and sustainable digital financial ecosystem for MSMEs.